Research on the Liability Identification of "Open Door Killing" Traffic Accidents - Li, Qianlin (International Journal of Social Sciences and Public Administration, 2024)
In legal practice, there is a great dispute about the liability identification of the "open door killing" accident. Often, the division of responsibility involves multiple parties, including the driver of the motor vehicle, the passenger of the vehicle, and possibly third parties. Therefore, this paper aims to propose a more reasonable liability division and compensation scheme through the analysis of the existing theories. First of all, this paper discusses three legal theories: subjective co-theory, objective co-theory and compromise theory. The subjective joint theory holds that the accident liability should be distributed according to the subjective faults of each party. The objective common theory focuses on the objective behavior and result of the parties in the accident. The compromise theory tries to find a balance between the first two, taking into account both subjective negligence and objective results. Combining these three theories, this paper proposes that in the "open-door killing" accident, the main body of responsibility should include motor vehicle driver and passenger. The driver of a motor vehicle should be responsible for ensuring safety after stopping, while the passenger should ensure that there is no traffic or pedestrians before driving. In addition, this paper also puts forward the shared responsibility of the duty of care, and believes that drivers and passengers should pay attention to the surrounding traffic environment to prevent possible accidents. Finally, this paper discusses the problem of identifying the accident in the accident. In determining whether an accident is an accident, consideration should be given to the degree of control over the accident by the parties. If both the driver and the passenger had sufficient ability to anticipate and prevent an accident, then the accident should not be considered an accident. Through the above analysis, this paper aims to provide a more comprehensive and fair perspective to guide the identification of liability and liability for compensation in practice. It is hoped that through this way, the traffic accidents caused by passengers' driving doors can be fundamentally reduced and the overall safety of road traffic can be improved.